Esophageal Wound Vacuum Placement for Anastomotic Leak: Lessons Learned From First Time Use at a Tertiary Care Center. Issue 3 (5th August 2021) - Glait, Megan; Wong, Jonathan; Krasaelap, Amornluck; Wagner, Amy; Lal, Dave; Schneider, John; Lerner, Diana
Abstract : Esophageal atresia and tracheoesophageal fistula (TEF) are rare birth anomalies typically requiring corrective surgery over the first few months of life. Esophageal surgery can lead to a life-threatening anastomotic leak. Esophageal wound vacuums have seen increased use in adults and one cohort of children as a therapeutic modality. This case study explores a tertiary care pediatric hospital's introductory experience in utilizing this technique. A 19-month-old male underwent staged repair for esophageal atresia/tracheoesophageal fistula requiring an esophageal stricture resection with primary anastomosis. An anastomotic leak was successfully managed with wound vacuums. Our experiences highlighted the need for individualized treatment plans with this therapy based on feeding capabilities, side effects of the vacuum, placement method, and replacement strategies.